Disaster Response Team Preparedness in Al Madina Islamic Junior High School (Public Health Perspective Journal, 2020)
Indonesia is a disaster prone country since it is located in the most active disaster area in the world. In 2018, a total of 2.571 disasters occurred in Indonesia where the highest rate of disasters was in Central Java (22,5%) and it increased in the beginning of 2019 (34,9%). Semarang City as the center of provincial government is an area with multiple disaster threats which has a high class of Disaster Risks Index (DRI), has experienced an increasing disaster incidence over past 5 years. It was targeted to decrease the DRI by 30% in 2019, one of them is by conducting disaster awareness program in schools, including Al Madina Islamic Junior High School. However, the preparedness of the team has not been optimal. Therefore, a study was conducted to determine the effectiveness of emergency response skills as an effort to increase the capacity of disaster response team. This is a descriptive quantitative study, samples were 85 students. Data collection technique used instruments of observation sheets, test, and interview. Data were processed through editing, scoring, and tabulating, while data were analyzed with univariate analysis. The results showed that respondents’ skills were increased and it was showed by faster emergency simulation and drill. The knowledge was also increased to 76% with the average score of pre-test was 39 and post-test was 66 after emergency response training. This study concluded that emergency response training is effective to increase skill and knowledge of disaster response team in Al Madina Islamic Junior High School.